The Assyrian rock relief at Yagmur (Evrihan) in the Tur Abdin - Genç, Bülent, (Archaeopress Archaeology, 2023)
This study publishes a newly discovered rock relief in the Mazidagi Plain, at the western end of the Tur Abdin in southeastern Turkey. The preserved remains include an image of an Assyrian king, divine symbols and traces of three panels of cuneiform inscription.